2013
DOI: 10.1017/s0269888913000325
|View full text |Cite
|
Sign up to set email alerts
|

A survey of different approaches to support in argumentation systems

Abstract: In the last decades, most works in the literature have been devoted to study argumentation formalisms that focus on a defeat relation among arguments. Recently, the study of a support relation between arguments regained attention among researchers; the bulk of the research has been centered on the study of support within the context of abstract argumentation by considering support as an explicit interaction between arguments. However, there exist other approaches that take support into account in a different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 46 publications
(211 reference statements)
1
63
0
Order By: Relevance
“…The distinction between deductive and necessary support has appeared first. Then, several interpretations have been given to the necessary support (sub-argument relation [26], evidential support [23][24][25], backing support [13]). …”
Section: Definition 4 (Bas)mentioning
confidence: 99%
See 2 more Smart Citations
“…The distinction between deductive and necessary support has appeared first. Then, several interpretations have been given to the necessary support (sub-argument relation [26], evidential support [23][24][25], backing support [13]). …”
Section: Definition 4 (Bas)mentioning
confidence: 99%
“…In [8], the support relation is left general so that the bipolar framework keeps a high level of abstraction. However there is no single interpretation of the support, and a number of researchers proposed specialized variants of the support relation: deductive support [5], necessary support [21,22], evidential support [23,24], backing support [13]. Each specialization can be associated with an appropriate modelling using an appropriate complex attack.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We refer the reader to the original papers for further details and to [30] for a survey on various types of support in argumentation. To summarize this section, research on bipolar argumentation frameworks has certainly demonstrated that going beyond the attack relation is interesting and useful.…”
Section: Definition 5 a Bipolar Argumentation Framework (Baf) Is A Tmentioning
confidence: 99%
“…Still, this approach is quite expressive, subsumes many other approaches to non-monotonic reasoning, and provides an active research field. Many research topics have been spawned around these frameworks including, among others, semantical issues [3], extensions on support [8], algorithms [7], and systems [23].…”
Section: Introductionmentioning
confidence: 99%